2013
DOI: 10.1002/art.38076
|View full text |Cite
|
Sign up to set email alerts
|

RBP‐Jκ–Dependent Notch Signaling Is Required for Murine Articular Cartilage and Joint Maintenance

Abstract: Objective Osteoarthritis (OA) is a degenerative disease resulting in severe joint cartilage destruction and disability. While the mechanisms underlying the development and progression of OA are poorly understood, gene mutations have been identified within cartilage-related signaling molecules implicating impaired cell signaling in OA and joint disease. The Notch pathway has recently been identified as a crucial regulator of growth plate cartilage development and components are expressed in joint tissues. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
4
49
0
Order By: Relevance
“…Recent evidence have revealed that the Notch pathway function as a potential regulator of both catabolic and anabolic molecules in the cartilage extracellular matrix during development [27]. Activation of Notch pathway is crucial for OA development [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence have revealed that the Notch pathway function as a potential regulator of both catabolic and anabolic molecules in the cartilage extracellular matrix during development [27]. Activation of Notch pathway is crucial for OA development [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…AOS is an autosomal dominant disorder caused by mutations in RBPJ and/or NOTCH1 genes resulting in Notch LOF, although no additional molecular mechanisms underlying this disease are known (Hassed et al, 2012;Stittrich et al, 2014). Notch signaling defects, either GOF or LOF, have also been implicated in osteoarthritis (Mahjoub et al, 2012;Hosaka et al, 2013;Mirando et al, 2013;Sassi et al, 2014;Liu et al, 2015), rheumatoid arthritis (Nakazawa et al, 2001;Park et al, 2015) and osteoporosis (Engin et al, 2008;Hilton et al, 2008;Majewski et al, 2011;Simpson et al, 2011), and have been associated with a predisposition to pathologic fractures (Kung et al, 2010). Studies like the one presented here further our understanding of the molecular players and events that Notch signaling might control during normal skeletal development, as well as our understanding of how they contribute to the pathology of certain skeletal diseases and injury processes.…”
Section: Discussionmentioning
confidence: 99%
“…57 In a further illustration of the complexity of Notch signalling, the early loss of RBPJκ in the limbbud mesenchyme does not affect joint development during embryogenesis, but leads to an early and progressive OAlike pathology. 60 As with the adult inactivation of RBPJκ, knockout of Sdc4 (the gene encoding syndecan4) in mice leads to nearly complete protection from development of OA fol lowing surgical destabilization of the knees. 61 However, the loss of SYND4 has only minimal effects on embry onic skeletal development, although it clearly affects bone regeneration through endochondral ossification, result ing in impaired fracture healing in adults.…”
Section: Developmental Pathways In Oamentioning
confidence: 99%